2019
DOI: 10.3389/fphys.2019.00867
|View full text |Cite|
|
Sign up to set email alerts
|

Psychophysiological Patterns Related to Success in a Special Operation Selection Course

Abstract: Actual theaters of operations require fast actions from special operations units with a high level of readiness and survival. Mission accomplishment depends on their psychological and physiological performance. The aim of the present study was to analyze: (1) the physical parameters related with success in a special operation selection course; and (2) the modifications of the psychological profile of recruits before and after a special operation selection course. Fifty-five male soldiers of the Spanish Army (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Specifically in air force crews, previous research found how exposure to normobaric hypoxia training produced psychophysiological changes in sympathetic nervous system modulation, cortical arousal levels, and increments in stress hormones such as cortisol and testosterone levels among others [3,[10][11][12][13][14][15][16][17]. In this line, research on paratrooper also showed how high-altitude jumps (High Altitude Low Opening and High Altitude High Opening) produced an increase in the physiological response and sympathetic modulation in both jumps, according to the stress responses theory exposed by Selye [18], and a decrease in cortical arousal, which is a symptom of central nervous system (CNS) fatigue only in the HAHO jump, showing that both types of jumps are stressful stimuli for the paratroopers; besides, tactical automatic parachute jumps produced an increase in cortisol hormone production that is related with the activation of the fight-flight response that increases the sympathetic autonomic modulation [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in air force crews, previous research found how exposure to normobaric hypoxia training produced psychophysiological changes in sympathetic nervous system modulation, cortical arousal levels, and increments in stress hormones such as cortisol and testosterone levels among others [3,[10][11][12][13][14][15][16][17]. In this line, research on paratrooper also showed how high-altitude jumps (High Altitude Low Opening and High Altitude High Opening) produced an increase in the physiological response and sympathetic modulation in both jumps, according to the stress responses theory exposed by Selye [18], and a decrease in cortical arousal, which is a symptom of central nervous system (CNS) fatigue only in the HAHO jump, showing that both types of jumps are stressful stimuli for the paratroopers; besides, tactical automatic parachute jumps produced an increase in cortisol hormone production that is related with the activation of the fight-flight response that increases the sympathetic autonomic modulation [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There are some professions that elicit a large stress response, modifying the homeostasis of the natural organism. In professions such as the military, police, firefighting, and even among elite athletes, individuals frequently experience stress responses beyond the body’s natural limits [ 2 , 3 , 4 ]. However, stress is not only present in these professions; medical personnel, drivers, journalists, and even teachers and students exhibit elevated stress levels as a result of their exposure to their work context [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors not measured in this study could have a greater influence on the self-confidence of participants, such as mistakes committed previously in other matches [ 18 , 46 ], and are advised to be included in future research. In this line, somatic anxiety is also affected by the individual subjectivity, as previous studies reported how perceived arousal levels are not related to the objective measured arousal [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sports competitions are a source of stress that provoke different neuroendocrine responses depending on the competitive moment: before, during, and after the competition [ 15 , 16 , 17 , 18 , 19 ]. An increase in cortisol (C) and sympathetic autonomic branch has been observed prior competitions, highlighting the anticipatory response prior to the competition due to the psychological anticipation influenced by Competitive State Anxiety Inventory-2 (CSAI-2) factors about subjective feelings of anxiety and confidence [ 20 , 21 , 22 , 23 ]. The anticipatory stress response can be observed from days before the stressor [ 24 , 25 ], but it is when the competitions approach that we find the biggest manifestations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%